Aristocratic neo-Gothicism in fourteenth-century Iberia: the case of Count Pedro of Barcelos - Queimada e Silva Tiago Joao (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
One of the main arguments used to legitimise Christian military expansion in medieval Iberia was the location of the origin of the Christian Iberian kingdoms in the ancient Visigothic Kingdom of Toledo (507-711), which established a notion of political continuity between these entities. The legitimacy of the Visigothic Kingdom was reflected in the polities that emerged out of the process of Christian expansion, enabling military activity against Muslims to be portrayed as the restoration of Gothic Spain. In the present study, I refer to this view of the past, especially in thirteenth-century Castilian royal historiography, as the neo-Gothic myth. The neo-Gothic myth was an asset held by royalty in the cultural enactment of these social struggles. In this article, I inquire into the reaction of the seignorial aristocracy to the royalty's neo-Gothic claims, using the historiographical work by Count Pedro of Barcelos (c. 1285-1354). More specifically, I analyse how Count Pedro adapted the neo-Gothic myth to an aristocratic perspective.